Will financial development and clean energy utilization rejuvenate the environment in BRICS economies? - Zoaka, Joshua Dzankar; Ekwueme, Daberechi Chikezie; Gungor, Hasan; Alola, Andrew Adewale (Wiley, 2022)
Global warming and environmental degradation caused essentially by changes in climate have attracted enormous surveillance considering the menace of its reverberation on the health of humans during the past two decades. Utilization of energy and financial development (FD) are among the key drivers of climatic change. Thus, using second-generation panel cointegration (the Westerlund, 2007 error-correction model), pooled mean group autoregressive distributive lag model (PMG-ARDL), and the panel dynamic ordinary least square (PDOLS) estimation techniques, the paper scrutinized the nexus between financial development, clean energy usage, economic growth, and environmental quality (proxied by CO2 emissions) of BRICS countries starting from 1980 to 2018. The findings from the study reveal that economic growth and labor force participation, in the long run, deteriorate the environmental quality by increasing the effusion of carbon. Contrarily, financial development, industrialization, trade openness, and renewable energy usage enhance the environmental quality of BRICS countries in the long run. In the short run, financial development was found to have a significant positive impact on the environmental quality of Brazil, China, and Russia, while it is negative for South Africa and India. The outcome of the PVECM Granger causality test reveals a two-way Granger causality that runs from renewable energy to carbon emissions in the short run. The policy implication of this study is that the government of BRICS countries needs to concentrate on improving their clean energy sources and also work on their industries. The BRICS nations' governments should formulate financial and trade policies that promote a sustainable environment and economic development.
Keywords: BRICS countries; environmental sustainability; financial development; renewable energy; trade